HUBUNGAN ANTARA CARING DAN KOMUNIKASI TERAPEUTIK DENGAN KUALITAS PELAYANAN KEPERAWATAN - Irbah Muthmainah Indarti Putri; Kristina Everentia Ngasu (Nusantara Hasana Berdikari, 2021)
Nursing services are an integral part of hospital health services, which have a very strategic position in an effort to improve the quality of customer service who comes to the hospital. The purpose of this systematic review is to determine the relationship between caring and therapeutic communication with the quality of nursing services. The method used to search for the article database consisted of quantitative studies collected from the scholar database published in 2015-2020. The results show that caring is good so that patients feel satisfied and therapeutic communication is good so that patients feel satisfied with the quality provided in nursing services. The conclusion is that the quality of health services has an influence on the frequency of patient satisfaction, the better the quality of health services, the better the frequency of patient satisfaction levels. Thus, there is a significant relationship between caring and therapeutic communication with the quality of nursing services.